Strata-Mapping the Detroit River Border with the Hamilton Perambulatory Unit - Ng-Chan, Taien (Intermédialités / Intermediality, 2019)
The Hamilton Perambulatory Unit (HPU)’s strata-mapping framework is an experimental research-creation practice that focuses on how spatial meaning is created through a performative “stratigraphic” sensing and researching of a site. The international border between Detroit, Michigan and Windsor, Ontario makes an especially compelling site for experimental cartographies in light of the conflicts over borders and walls in the current political environment. At the southernmost tip of the Great Lakes system, we focused our attention on this river border as a material site and geopolitical space: it enabled us to investigate alternate possibilities for sensing and envisioning the layered and conjoined histories of this fluid space. The Ojibwe name for this location is waawiiatanong ziibi, “where the river bends,” suggesting a radically different spatial imaginary than the divided space that has been established through colonial and national histories. Experimental cartographies can thus help to develop alternate ways of experiencing such sites, an initial step towards decolonizing the spatial imaginary through a project of delinking. In September 2018, we conducted a workshop entitled Buoyant Cartographies, focusing on a performative and intermedial investigation into spatial meanings and their construction on Peche Island, which sits in the middle of the Detroit River. This was one of three Detroit River sites investigated in the workshop, with contributions from workshop organizers and HPU co-conspirator Donna Akrey.